2021
DOI: 10.3390/app11020656
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time PCR Confirms Infection with Lagovirus europaeus

Abstract: Lagovirus europaeus GI.1/GI.2 is an etiological agent causing the highly dangerous rabbit hemorrhagic disease (RHD). Molecular research is the basic tool today that can help solve epidemic problems related to the expansion of pathogens in the world. By using the real-time polymerase chain reaction technique (PCR), we detected three different strains of Lagovirus europaeus/GI.1, which is an RNA virus infecting mainly rabbits. The results showed that the method used was fast, very specific, and effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…compared to the control. The same result regarding the upregulation of Bcl-2 family proteins (determined at the level of Bax and Bcl-2 mRNA) in the liver tissue and in the spleen and kidneys after infection of rabbits with the L. europaeus GI.2 genotype was obtained by Bebnowska et al (2023Bebnowska et al ( , 2024. In our lung and spleen results, the Bax mRNA gene expression level indicates a lower degree of apoptosis (statistically insignificant).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…compared to the control. The same result regarding the upregulation of Bcl-2 family proteins (determined at the level of Bax and Bcl-2 mRNA) in the liver tissue and in the spleen and kidneys after infection of rabbits with the L. europaeus GI.2 genotype was obtained by Bebnowska et al (2023Bebnowska et al ( , 2024. In our lung and spleen results, the Bax mRNA gene expression level indicates a lower degree of apoptosis (statistically insignificant).…”
Section: Discussionsupporting
confidence: 83%
“…Chen et al (2018) found that non-structural protein 6 (NSP6)-induced Caspase-3 activity in Oryctolagus cuniculus kidney cells (RK13). However, other studies showed a significant increase in Caspase-3 mRNA in rabbit liver (Bebnowska et al, 2024) and cleaved protein Caspase-3 in lung, heart, kidney, and spleen during infection with the L. europaeus GI.2 genotype (Bebnowska et al, 2023). This methodological approach is better for measuring apoptosis levels/ activity biomarkers (Caspase-3, PARP, and Bax/Bcl-2 proteins).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This method has been shown to be 100% sensitive and to detect 10 copies of the virus per well. The test uses a liver fragment from an infected rabbit, from which a homogenate is then made ( 131 ).…”
Section: Lagovirus Europaeusmentioning
confidence: 99%
“…Despite the high virulence and rapid spread of Lagovirus europaeus, there is currently no in vitro culture system for these viruses. Consequently, vaccines are based on inactivated virus isolated from infected rabbits, offering limited crossimmunity between the two strains [6,7].…”
Section: Introductionmentioning
confidence: 99%